Kehidupan sebagai Metodologi Penelitian: Analogi Reflektif antara Proses Penulisan Tugas Akhir dan Pencarian Makna Hidup - Achmad Farouq Abdullah; Masruin Masad; Nesa Novrizal; Andi Aziz (LP3M IAI Al Urwatul Wutsqo Jombang, 2026)
This article examines the structural analogy between scientific research methodology and the human search for meaning in life through a reflective literature review. Drawing on a systematic screening of 127 records (2020–2025), of which 42 met the inclusion criteria, the study integrates Kolb's (1984) experiential learning, Schön's (1983) reflective practice, and existentialist perspectives from Sartre, Kierkegaard, and Frankl. Thematic coding followed a six-phase procedure (Braun & Clarke, 2006), with inter-rater verification between two coders (Cohen's κ = 0.81) to mitigate interpretive subjectivity. Findings demonstrate that the seven stages of academic research—problem formulation, conceptual framework, method selection, data collection, analysis, revision, and conclusion—exhibit an empirically traceable correspondence with existential phases of human development, rather than a purely metaphorical parallel. The study proposes the Integrative Methodology–Life Analogy (IMLA) framework as an original contribution. Pedagogical implications are discussed with explicit attention to institutional constraints in Indonesian higher education, avoiding prescriptive generalization